On the great patriotic war of the Soviet Union : speeches, orders of the day, and answers tot foreign press correspondents - Stalin, Jozef (London New York Melbourne : Hutchinson, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; Sovjet-Unie.